THE COMPARISON CLASS AVERAGE OF TWO GENERATIONS OF NURSING STUDENTS AT MOLUCCAS CHRISTIAN UNIVERSITY OF INDONESIA: (Perbandingan nilai rata rata kelas 2 Angkatan pd mahasiswa Keperawatan di Universitas Kristen Indonesia Maluku) - Harsono, Debora (Uniqbu Journal of Exact Sciences, 2021)
This paper presents a fact about the Class Average of Two Generations ( 2011 and 2012 generations). It consists of five classes, includes Extension, A, B, C, and D. But the writer would like to analyze one class only, namely D class. Because the average class data stated, there is a drastic increasing point. To achieve the credibility of this research, the researcher uses average class data from another generation. So, the writer does the comparison process between 2011 and 2012 generations. Finally, through this paper, we can prove that some factors influenced the class average of two generations from D classes on nursing students at the Moluccas Christian University of Indonesia. Shortly, we can conclude that the D class of the 2012 generation has a higher class average point than the 2011 generation.